Compression-resistant nano carbon-based thin film material as well as preparation method and application thereof

The compression-resistant nanocarbon-based film material prepared by the centrifugal casting process utilizes the gradient distribution of carbon nanotubes and graphene of different sizes to solve the problems of insufficient thermal conductivity and poor mechanical resilience of the existing carbon nanotube/graphene composite structure in chip packaging, and achieves efficient heat transfer and material applicability.

CN120620772APending Publication Date: 2025-09-12SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510673783.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The existing carbon nanotube/graphene composite structure has problems with insufficient thermal conductivity and poor mechanical resilience in chip packaging. It cannot meet the requirements of horizontal heat distribution followed by vertical heat dissipation, and is easily damaged during compression.

Method used

A centrifugal casting process is used to prepare compression-resistant nano-carbon-based thin film materials. By setting a three-dimensional network structure of carbon nanotubes and a gradient distribution of graphene of different sizes in the middle layer, a double-continuous gradient structure is formed, which enhances the compressibility and interface bonding of the material and provides more phonon transmission channels.

Benefits of technology

The material achieves efficient horizontal and vertical thermal conductivity in a compressed state, improves the material's applicability and compression resistance, solves the problems of insufficient thermal conductivity and poor mechanical resilience, and is suitable for thermal management in chip packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120620772A_ABST
    Figure CN120620772A_ABST
Patent Text Reader

Abstract

The invention discloses a compression-resistant nano carbon-based thin film material as well as a preparation method and application thereof. The thin film material comprises a first nano carbon layer, a middle layer and a second nano carbon layer which are sequentially arranged in a stacked mode in the designated direction. The first nanocarbon layer and the second nanocarbon layer are formed by first graphene, the middle layer is a composite layer of the first graphene, the second graphene and carbon nanotubes, the lamellar size of the first graphene is larger than that of the second graphene, and the distribution density of the first graphene in the middle layer is gradually reduced in the direction away from an interface. Good horizontal soaking of the contact position of the material and a heat source can be achieved, good interface bonding between layers can be achieved due to the arrangement of the gradient trend, the three-dimensional heat conduction network, composed of the carbon nanotubes and the two kinds of graphene of different sizes, of the middle layer is more beneficial to providing more phonon transmission channels, heat transfer is accelerated, and the heat transfer efficiency is improved. The problems that an existing graphene carbon nanotube composite material is insufficient in thermal conductivity and poor in mechanical resilience can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano-carbon composite materials, and in particular to a compression-resistant nano-carbon-based film material, a preparation method thereof, and applications thereof. Background Art

[0002] With the active deployment of 6G and the gradual shift towards high power and high density in various electronic devices, the demand for chip performance is increasing. However, with the slowdown of Moore's Law, chip integration is becoming a new development trend, breaking through the computing power limits of a single processor. In chip integration technology, multiple chips on a wafer need to be heated horizontally and then dissipated vertically, which puts new demands on 3D high-thermal conductivity materials.

[0003] Thermal interface materials mainly improve the heat transfer efficiency by filling the gap between the device's heat source and the heat sink. Therefore, for packaging, thermal interface materials must not only take into account horizontal and vertical thermal conductivity, but also have a certain degree of compressibility to compensate for package assembly deviations. The in-plane thermal conductivity of graphene at room temperature is as high as 5300W m -1 K -1 , and has good thermal stability. The thermal conductivity of carbon nanotubes can reach 3000-3500W m at room temperature. -1 K -1 , and has good flexibility. Therefore, graphene and carbon nanotubes, with their excellent thermal and mechanical properties, are considered ideal new interface materials. In addition to their great potential in thermal conductivity, carbon nanotubes and graphene also have good electromagnetic shielding properties, making them more advantageous than traditional materials. Existing research on the dual functions of thermal conductivity and electromagnetic shielding of nanocarbon thermal interface materials has also demonstrated the excellent performance of the materials and a wide range of application scenarios, such as IGBT packaging, wearable electronic devices, military, 5G communications and other fields.

[0004] Existing carbon nanotube / graphene composite structures include the following: array structures, sandwich structures, three-dimensional network structures, and continuous gradient structures. In their research on array structures, Gao Chao's team at Zhejiang University used a boundless microfilament shearing technique, where microfilaments move vertically, creating a huge vertical shear force. This allowed them to precisely orient giant graphene oxide sheets (with radial dimensions greater than 100 microns). After impregnating this vertical array with a silicone matrix, the composite material demonstrated a record-breaking power of 94 W m-2 at only 14.8 vol% filler. -1 K -1 In the study of sandwich structures, Lin Zhengde's team at Ningbo Institute of Materials constructed a three-layer thermal interface material by using vertically arranged graphene in the middle and micron-thick liquid metal on the upper and lower surfaces. Its longitudinal thermal conductivity reached 176W m -1 K-1 (Nano-Micro Letters, 2023, 15, 9). In the study of three-dimensional network structures, Zhang Yongyi's research group at the Suzhou Institute of Nano-Tech and Nano-Bionics, Chinese Academy of Sciences, developed a method for constructing a three-dimensional interconnected high-thermal conductivity network structure. They used continuous pulling and dip-coating to prepare highly oriented and dense carbon nanotube@graphene oxide (CNT@GO) coaxial fibers. After arranging them in an orderly and tight manner and hot pressing them, they achieved a high degree of three-dimensional interconnection of highly crystalline oriented graphene nanosheets, thereby obtaining a new type of thermal conductive structure with high consistency and density. The unique structure of the constructed carbon nanotube-graphene film (CGF) provides a three-dimensional heat transfer path, and the thermal conductivity in the horizontal and vertical directions can reach 804.9W m -1 K -1 and 63.8W m -1 K -1 , which is conducive to efficient three-dimensional heat dissipation (Carbon 2023, 208, 322329).

[0005] However, existing research on carbon nanotube / graphene three-dimensional thermal conductivity still suffers from poor controllability of basic unit orientation and insufficient phonon transmission channels, which cannot well meet the requirements of thermal conductive materials in chip packaging to first average heat horizontally and then dissipate heat vertically.

[0006] In addition, in the chip packaging of electronic products, in order to ensure close bonding and improve the level of interface heat transfer, mechanical stress compression of the thermal conductive medium is often required to achieve close contact, while also being able to compensate for assembly deviations during the packaging process. However, the current graphene-carbon nanotube composite materials have limited compression resistance and are often compressed and damaged in actual application scenarios, greatly reducing their original high thermal conductivity. Summary of the Invention

[0007] In view of the deficiencies in the prior art, the present invention aims to provide a compression-resistant nano-carbon-based film material, a preparation method thereof and applications.

[0008] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:

[0009] In a first aspect, the present invention provides a compression-resistant nano-carbon-based thin film material, which comprises a first nano-carbon layer, an intermediate layer, and a second nano-carbon layer stacked in sequence along a specified direction;

[0010] The first nano-carbon layer and the second nano-carbon layer are formed by stacking multiple layers of the first graphene along the specified direction, the intermediate layer is a composite layer of the first graphene, the second graphene and carbon nanotubes, and the sheet size of the first graphene is larger than that of the second graphene;

[0011] In the intermediate layer, the carbon nanotubes form a three-dimensional network structure, and at least part of the carbon nanotube fragments extend in the specified direction, the second graphene is attached to the surface of the carbon nanotubes, the first graphene is filled in the three-dimensional network structure, and at least at the interface between the intermediate layer and the first nano-carbon layer and the second nano-carbon layer, the distribution density of the first graphene in the intermediate layer has a decreasing trend away from the interface.

[0012] In a second aspect, the present invention further provides a method for preparing a compression-resistant nano-carbon-based film material, comprising:

[0013] Providing a first dispersion and a second dispersion, wherein a first graphene precursor is dispersed in the first dispersion, a second graphene and carbon nanotubes are dispersed in the second dispersion, and a sheet size of the first graphene precursor is larger than a sheet size of the second graphene;

[0014] Using centrifugal casting, sequentially forming a first nanocarbon layer precursor from a first dispersion, forming an intermediate layer precursor from the first dispersion and a second dispersion, and further forming a second nanocarbon layer precursor from the first dispersion to obtain an initial assembly, and when forming the intermediate layer precursor, adjusting at least the flow rate of the first dispersion in a time sequence so that the distribution density of the first graphene precursor in the intermediate layer precursor has a decreasing trend away from the interlayer interface;

[0015] performing a carbonization expansion treatment on the initial assembly to obtain a carbonized assembly;

[0016] The carbonized assembly is graphitized to obtain a compression-resistant nano-carbon-based film material, wherein the first graphene precursor is converted into the first graphene.

[0017] In a third aspect, the present invention further provides the use of the above-mentioned compression-resistant nano-carbon-based film material in chip packaging.

[0018] In a fourth aspect, the present invention also provides a chip packaging structure, which includes a chip, the above-mentioned compression-resistant nano-carbon-based film material and a heat sink, wherein the compression-resistant nano-carbon-based film material is tightly filled between the chip and the heat sink, and the compression-resistant nano-carbon-based film material is in a state of mechanical compression. Usually, in order to meet application requirements, the chip can be provided with multiple compression-resistant nano-carbon-based film materials to achieve common heat dissipation.

[0019] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention include at least:

[0020] The technical solution provided by the present invention is based on carbon nanotubes and graphene, two highly thermally conductive materials, to develop a compression-resistant nano-carbon-based thin film material. A macroscopic sandwich structure is added to the previously constructed three-dimensional thermal conductive network structure, and a gradient change trend of the component ratio is set at the sandwich interface. The addition of the sandwich structure can achieve better horizontal heat distribution at the contact position between the material and the heat source, and the setting of the gradient trend at the sandwich interface can achieve better interface bonding between layers. The three-dimensional thermal conductive network composed of carbon nanotubes and two different sizes of graphene in the middle layer is more conducive to providing more phonon transmission channels to accelerate heat transfer, which can solve the problems of insufficient thermal conductivity and poor mechanical resilience of existing graphene-carbon nanotube composite materials.

[0021] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of this application and implement them according to the contents of the specification, the following is an explanation of the preferred embodiments of the present invention with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a structural diagram of an initial assembly provided by a typical embodiment of the present invention;

[0023] Figure 2 This is a schematic structural diagram of a compression-resistant nano-carbon-based film material provided by a typical embodiment of the present invention;

[0024] Figure 3 Schematic diagram of flow control of a preparation method provided by a typical embodiment of the present invention;

[0025] Figure 4 This is a macroscopic photograph of an initial assembly provided by a typical embodiment of the present invention;

[0026] Figure 5 This is a macroscopic photograph of a carbonized assembly provided by a typical embodiment of the present invention;

[0027] Figure 6 This is a macroscopic photograph of pure graphene oxide material after carbonization under the same conditions, provided in a typical embodiment of the present invention;

[0028] Figure 7 This is an electron microscope photograph of the cross-sectional morphology of a carbonized assembly provided in a typical embodiment of the present invention;

[0029] Figure 8 This is an electron microscope photograph of the cross-sectional morphology of the intermediate layer in the carbonized assembly provided in a typical embodiment of the present invention;

[0030] Figure 9 This is an electron microscope photograph of a graphene sheet in a three-dimensional network in an intermediate layer of a carbonized assembly provided in a typical embodiment of the present invention;

[0031] Figure 10 This is an electron microscope photograph of the cross-sectional morphology of a graphene oxide layer in a carbonized assembly provided in a typical embodiment of the present invention;

[0032] Figure 11 This is a compression performance test diagram of a compression-resistant nano-carbon-based film material provided by a typical embodiment of the present invention;

[0033] Figure 12 This is a comparative test chart of the thermal conductivity of a compression-resistant nano-carbon-based film material and other nano-carbon materials provided in a typical embodiment of the present invention;

[0034] Figure 13 This is a comparative test chart of the thermal conductivity of products of compression-resistant nano-carbon-based film materials at different processing temperatures provided by a typical embodiment of the present invention;

[0035] Figure 14 This is a comparative test chart of the electromagnetic shielding performance of the compression-resistant nano-carbon-based film material provided by a typical embodiment of the present invention at different processing temperatures;

[0036] Figure 15 The absorption efficiency (SE) of the product of the compression-resistant nano-carbon-based film material provided by a typical embodiment of the present invention at different processing temperatures is A ), reflection efficiency (SE R ) and total shielding effectiveness (SE T )Comparison test chart. DETAILED DESCRIPTION

[0037] Existing carbon nanotube and graphene composite structures mainly include: array structure, sandwich structure, three-dimensional network structure, continuous gradient structure and nanoscale three-dimensional thermal conductive sandwich gradient network structure. Existing structures still have the following problems:

[0038] (1) Although the array structure can well utilize the excellent thermal conductivity of carbon nanotubes and graphene in a certain direction, in the field of thermal management, as a thermal conductive material, it cannot transfer heat from the heat source to the entire material evenly, resulting in local overheating of hot spots.

[0039] (2) The sandwich structure can meet some of the requirements of core particle encapsulation, but the traditional sandwich structure still cannot solve the problem of interface bonding between different layers. When the sandwich structure material is thermally reduced or treated at high temperature, as a large number of gas molecules are generated and the overflow channel is limited, it is very easy to produce micro-air pockets at the junction of the two interfaces, resulting in macroscopic stratification of the material after carbonization or graphitization. The thermal conductivity of the carbon nanotube / graphene sandwich structure composite material is limited by the thickness, that is, the material interface bonding and thermal conductivity will decrease with increasing thickness, thereby limiting the application of the material.

[0040] (3) Although the three-dimensional network structure can achieve simultaneous horizontal and vertical heat conduction, it cannot complete the rapid and uniform horizontal transfer of heat from the heat source to the entire material in the field of core particle packaging.

[0041] (4) The continuous gradient structure can solve the problem of discontinuous interlayer interfaces, but in the field of core particle packaging, it cannot simultaneously meet the requirements of good heat dissipation between the heat source and the thermal conductive material and between the thermal conductive material and the heat sink.

[0042] In view of the shortcomings of the prior art, the inventors of this case, after long-term research and extensive practice, have proposed the technical solution of the present invention. The following will further explain this technical solution, its implementation process and principles.

[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited to the specific embodiments disclosed below.

[0044] Moreover, relational terms such as “first” and “second” are merely used to distinguish one component or method step from another with the same name, but do not necessarily require or imply any actual relationship or order between these components or method steps.

[0045] Based on the above problems, the main technical concept of the present invention is to use a centrifugal casting process to prepare a compression-resistant nano-carbon-based thin film material, which combines the advantages of the above-mentioned structure. It maximizes the horizontal thermal conductivity of graphene and the excellent axial thermal conductivity of carbon nanotubes. After carbonization and graphitization treatment, micro-airbags are formed between the graphene layers, which makes the material as a whole have a certain compressibility and the carbon nanotubes between the graphene form a vertical array, increasing the overall vertical thermal conductivity of the material while improving the adaptability of the material in the packaging process. The small sheets of graphene in the structure are overlapped between the vertically arranged carbon nanotube arrays to form a better three-dimensional network structure.

[0046] According to the above-mentioned inventive concept, an embodiment of the present invention first provides a compression-resistant nano-carbon-based thin film material, which includes a first nano-carbon layer, an intermediate layer, and a second nano-carbon layer stacked in sequence along a specified direction; the first nano-carbon layer and the second nano-carbon layer are formed by multi-layer stacking of the first graphene along the specified direction, and the intermediate layer is a composite layer of the first graphene, the second graphene and carbon nanotubes, and the sheet size of the first graphene is larger than that of the second graphene; in the intermediate layer, the carbon nanotubes form a three-dimensional network structure, and at least part of the carbon nanotube fragments extend in the specified direction, the second graphene is attached to the surface of the carbon nanotubes, the first graphene is filled in the three-dimensional network structure, and at least at the interface between the intermediate layer and the first nano-carbon layer and the second nano-carbon layer, the distribution density of the first graphene in the intermediate layer has a decreasing trend away from the interface.

[0047] The compression-resistant nanocarbon-based film material described in the present invention comprises two layers of stacked graphene, with a middle layer comprising a nanoscale gradient structure composed of horizontally arranged graphene layers, carbon nanotubes vertically arranged between the graphene layers, and small graphene sheets lapped between the carbon nanotube arrays. The present invention utilizes carbon nanotubes, small graphene sheets, and graphene oxide, and undergoes a centrifugal casting process, carbonization, expansion, and graphitization treatment to create a dual-continuous gradient compression-resistant nanocarbon-based film material that not only exhibits both horizontal and vertical thermal conductivity, but also exhibits a certain degree of compression resistance and good interfacial bonding. The preparation method is efficient, scalable, and highly applicable, enabling large-scale, highly dense assembly of materials and promoting thermal management applications in chip packaging.

[0048] In some embodiments, the intermediate layer has a dual-continuous gradient structure, in which the distribution density of the carbon nanotubes attached with the second graphene has an increasing gradient along the specified direction from the first nanocarbon layer and the second nanocarbon layer to the central area of ​​the intermediate layer, and the distribution density of the first graphene has a decreasing gradient.

[0049] The double-continuous structure ensures that the density of the middle layer is basically uniform, and it is not easy to have problems with density differences along a specified direction. It is more excellent in improving stability, compression resistance, high thermal conductivity and high electromagnetic shielding properties.

[0050] In some embodiments, in a natural state where the compression-resistant nano-carbon-based thin film material is not compressed, the thickness of the first nano-carbon layer and the second nano-carbon layer is 150-300 μm, and the thickness of the intermediate layer is 400-800 μm.

[0051] In some embodiments, the sheet size of the first graphene is 3-5 μm, and the sheet size of the second graphene is 1-5 nm.

[0052] In some embodiments, the compression rate of the compression-resistant nano-carbon-based thin film material is 0.4-0.8 times.

[0053] A second aspect of the embodiments of the present invention further provides a method for preparing a compression-resistant nano-carbon-based film material, which comprises the following steps:

[0054] Providing a first dispersion and a second dispersion, wherein a first graphene precursor is dispersed in the first dispersion, a second graphene and carbon nanotubes are dispersed in the second dispersion, and a sheet size of the first graphene precursor is larger than a sheet size of the second graphene;

[0055] By centrifugal casting, the first dispersion is sequentially formed into a first nano-carbon layer precursor, the first dispersion and the second dispersion are jointly formed into an intermediate layer precursor, and the first dispersion is again formed into a second nano-carbon layer precursor to obtain an initial assembly having a structure as shown in FIG. Figure 1 As shown, it contains graphene oxide (first graphene precursor), small-sheet graphene (second graphene) and carbon nanotubes; and when forming the intermediate layer precursor, at least the flow rate of the first dispersion liquid is adjusted in a time sequence so that the distribution density of the first graphene precursor in the intermediate layer precursor has a decreasing trend away from the interlayer interface;

[0056] performing a carbonization expansion treatment on the initial assembly to obtain a carbonized assembly;

[0057] The carbonized assembly is graphitized to obtain a compression-resistant nano-carbon-based film material having a structure as shown below: Figure 2 As shown, it comprises a first graphene, a second graphene and a carbon nanotube, wherein the first graphene precursor is converted into the first graphene.

[0058] In a specific embodiment, the first graphene precursor may be graphene oxide, which is converted into graphene in a subsequent process. However, the present invention is not limited thereto. Other functionalized graphenes that can help disperse and be converted into graphene in a subsequent process are theoretically alternative options.

[0059] More preferably, in order to achieve the double continuous gradient as described above, in some embodiments, the complete process of centrifugal casting of the intermediate layer precursor is divided into a continuous first stage and a second stage, in which the flow rate of the first dispersion decreases and the flow rate of the second dispersion increases, and in the second stage, the flow rate of the first dispersion increases and the flow rate of the second dispersion decreases.

[0060] More specifically, in some embodiments, per unit time, the mass change gradient of the first graphene precursor carried by the first dispersion is equal to the total mass change gradient of the second graphene and carbon nanotubes carried by the second dispersion.

[0061] As for other specific process conditions, in some embodiments, the mass concentration of graphene oxide in the first dispersion is 2.5-3 mg / mL.

[0062] In some embodiments, the mass ratio of the second graphene to the carbon nanotubes in the second dispersion is 1:0.6-1.2, and the concentration of the second graphene is 2.5-3 mg / mL.

[0063] In some embodiments, during the centrifugal casting, the flow rate of the first dispersion and / or the second dispersion is in the range of 0-1.67 mL / min.

[0064] In some embodiments, the rotation speed of the centrifugal casting is 0-20000 rpm.

[0065] In some embodiments, the carbonization expansion treatment is performed in a protective atmosphere, with a maximum temperature of 1000-1800° C., a heating rate of 2-10° C. / min, and a holding time of 60-120 min.

[0066] In some embodiments, the graphitization treatment is performed in a protective atmosphere, with a maximum temperature of 2800° C., a heating rate of 2-10° C. / min, and a holding time of 60-120 min.

[0067] It should be noted that the above-mentioned process conditions are the window range of commonly used and more effective process conditions summarized by the inventors of the present invention in practice, but it does not mean that the technical effects claimed by the present invention cannot be achieved at all if these process conditions are exceeded. In fact, according to the technical ideas disclosed in the present invention, even if other process conditions are adjusted by themselves, it is still possible to obtain a composite material with the same structural characteristics and similar properties, which of course also falls within the scope of protection of the present invention.

[0068] In addition, a third aspect of the embodiments of the present invention further provides an application of the compression-resistant nano-carbon-based film material provided by any of the above-mentioned embodiments in chip packaging.

[0069] As a specific manifestation of application, the fourth aspect of an embodiment of the present invention also provides a chip packaging structure, which includes a chip, a compression-resistant nano-carbon-based film material provided by any of the above-mentioned embodiments, and a heat sink, wherein the compression-resistant nano-carbon-based film material is tightly filled between the chip and the heat sink, and the compression-resistant nano-carbon-based film material is in a state of mechanical compression.

[0070] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0071] Example 1

[0072] This embodiment illustrates a preparation process of a compression-resistant nano-carbon-based thin film material.

[0073] The materials used in this embodiment include:

[0074] 1. Graphene oxide: 10 mg / g monolayer graphene oxide aqueous dispersion was diluted to a concentration of 3 mg / mL.

[0075] 2. Small-sheet graphene: It is made of few-layer graphene nanosheets with a size of 1-5nm, and its concentration is 1:1 with the concentration of graphene oxide.

[0076] 3. Carbon nanotube dispersion: Prepared with 5 mg / g carbon nanotube slurry and mixed with small-sheet graphene to form a mixed solution with the same concentration as graphene oxide and small-sheet graphene.

[0077] The preparation process includes:

[0078] (1) Graphene oxide and single-walled carbon nanotubes + small-sheet graphene were prepared into two dispersions with a concentration of 1:1:1, and the dispersions were prepared by centrifugal casting using the following method: Figure 3 The material mass ratio change curve shown in FIG. 1 (the horizontal axis represents time, and the left and right vertical axes represent the mass ratio of graphene oxide input in the casting process and the total mass ratio of single-walled carbon nanotubes + small-sheet graphene) is used to prepare an initial compression-resistant nanocarbon-based film material with a double-continuous gradient structure in the middle layer, as shown in the photo. Figure 4 The interface bonding, thermal conductivity, and electromagnetic shielding performance of the film obtained in this step are analyzed to determine the optimal structure.

[0079] The specific conditions of this step are as follows: room temperature, a centrifugal casting speed of 15,000 rpm, an initial flow rate of graphene oxide at time t1 of 1.5 mL / min, the flow rate of the single-walled carbon nanotube + small-sheet graphene dispersion is adjusted as shown in the figure, the time of each period is adjusted according to the required film thickness, and the duration of each period is symmetrical around t3. The thickness of the formed graphene oxide layers is 40 μm, and the thickness of the intermediate layer precursor is 80 μm.

[0080] (2) The compression-resistant nano-carbon-based film material is subjected to carbonization treatment in an inert atmosphere, and the temperature is increased in the range of 20-1000°C at a rate of 2-10°C / min to obtain a carbonized assembly, the appearance of which is as follows: Figure 5As shown, for example Figure 6 The carbonized state of pure graphene oxide is shown, and the appearance is obviously different.

[0081] The cross section of the carbonized assembly obtained in this step is as follows Figure 7 As shown, the sandwich structure can be clearly seen; if you zoom in, you can see Figure 8 The middle layer structure shown in the figure shows a part of the carbon nanotube network structure that extends vertically. If you continue to zoom in, you can see Figure 9 The graphene sheets in the carbon nanotube network are shown in FIG. 1 , while the enlarged morphology of the graphene sheets of two layers of graphene oxide is shown in FIG. Figure 10 shown.

[0082] The expansion degree, compression performance, thermal conductivity and electromagnetic shielding performance of the film obtained in this step were analyzed and evaluated.

[0083] The final maximum temperature of this step is 1000°C and the duration is 60 min.

[0084] (3) The initial compression-resistant nano-carbon-based film material is graphitized at 2800°C in an inert atmosphere and a heating rate of 2-10°C / min in the range of 20-1000°C. The expansion degree, compression performance, thermal conductivity and electromagnetic shielding performance of the compression-resistant nano-carbon-based film material obtained in this step are analyzed and evaluated.

[0085] The final maximum temperature of this step is 2800°C and the duration is 60 minutes.

[0086] Figure 11 The compression performance test diagram of the compression-resistant nano-carbon-based film material obtained in this embodiment is shown, and its excellent compression resistance can be seen; Figure 12 The thermal conductivity comparison test chart shows the compression-resistant nanocarbon-based film material obtained in this example, pure graphene oxide, and an existing graphene oxide-carbon nanotube composite material (a membrane material prepared by centrifugal casting by directly mixing graphene oxide, small-sheet graphene, and carbon nanotube slurry without structural design. This material does not contain a sandwich structure or a bicontinuous gradient structure, but is simply a mixed membrane) after being graphitized at 2800°C. The significant improvement in thermal conductivity is evident. Figure 13 The thermal conductivity comparison test of the products obtained at different processing stages (the horizontal axis is the temperature corresponding to the different stages) is shown. It can be observed that the thermal conductivity improves successively with the successive steps. Figure 14 and Figure 15 This is a performance test of electromagnetic shielding performance at different processing stages (temperatures), and the same rules as thermal conductivity can also be observed.

[0087] Example 2

[0088] This embodiment is substantially the same as embodiment 1, the main difference being the adjustment of specific process conditions:

[0089] The centrifugal casting speed was 15,000 rpm, the graphene oxide concentration was 3 mg / mL, and the other components were prepared in a 1:1:1 ratio. The time of each stage was adjusted so that the thickness of the two pure graphene layers was 30 μm each and the thickness of the middle layer was 100 μm. The temperature of the carbonization expansion treatment was 1,000 ° C, the time was 60 min, and the temperature of the graphitization treatment was 2,800 ° C, the time was 60 min.

[0090] Example 3

[0091] This embodiment is substantially the same as embodiment 1, the main difference being the adjustment of specific process conditions:

[0092] The centrifugal casting speed was 15,000 rpm, the concentration of graphene oxide was 3 mg / mL, and the other components were prepared in a 1:1:1 ratio. The time of each stage was adjusted so that the thickness of the two pure graphene layers was 15 μm each and the thickness of the middle layer was 130 μm. The temperature of the carbonization expansion treatment was 1,000 ° C, the time was 60 minutes, and the temperature of the graphitization treatment was 2,800 ° C, the time was 60 minutes.

[0093] Based on the above embodiments, it can be seen that the embodiments of the present invention use a centrifugal casting process to prepare a compression-resistant nano-carbon-based film material, which can realize more phonon transmission channels. The gradient structure in the structure strengthens the bonding between the interfaces of different materials, so that the material has higher thermal conductivity in the horizontal and vertical directions. In the double-continuous gradient compression-resistant nano-carbon-based film material constructed by the present invention, the graphene layers stacked on the upper and lower surfaces provide horizontal thermal conductivity, evenly diffusing heat from the contact point to the entire material, and the carbon nanotubes provide vertical thermal conductivity and flexibility, thereby improving the applicability of the material. Small sheets of graphene are overlapped in the middle of the carbon nanotube array to provide more phonon transmission channels, and finally a three-dimensional high thermal conductivity material with high thermal conductivity, electromagnetic function and compressible performance is obtained, which solves the problems of low thermal conductivity, narrow operating temperature range and poor mechanical resilience of traditional thermal interface materials.

[0094] It should be understood that the above embodiments are merely illustrative of the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent variations or modifications made in accordance with the spirit and substance of the present invention are intended to be encompassed within the scope of protection of the present invention.

Claims

1. A compression-resistant nano-carbon-based film material, characterized in that: It includes a first nano-carbon layer, an intermediate layer, and a second nano-carbon layer stacked in sequence along a specified direction; The first nano-carbon layer and the second nano-carbon layer are formed by stacking multiple layers of the first graphene along the specified direction, the intermediate layer is a composite layer of the first graphene, the second graphene and carbon nanotubes, and the sheet size of the first graphene is larger than that of the second graphene; In the intermediate layer, the carbon nanotubes form a three-dimensional network structure, and at least part of the carbon nanotube fragments extend in the specified direction, the second graphene is attached to the surface of the carbon nanotubes, the first graphene is filled in the three-dimensional network structure, and at least at the interface between the intermediate layer and the first nano-carbon layer and the second nano-carbon layer, the distribution density of the first graphene in the intermediate layer has a decreasing trend away from the interface.

2. The compression-resistant nano-carbon-based film material according to claim 1, characterized in that: The intermediate layer has a double continuous gradient structure. In the double continuous gradient structure, along the specified direction from the first nanocarbon layer and the second nanocarbon layer toward the central area of ​​the intermediate layer, the distribution density of the carbon nanotubes attached with the second graphene has an increasing change gradient, and the distribution density of the first graphene has a decreasing change gradient.

3. The compression-resistant nano-carbon-based film material according to claim 1, characterized in that: In a natural state where the compression-resistant nano-carbon-based film material is not compressed, the thickness of the first nano-carbon layer and the second nano-carbon layer is 150-300 μm, and the thickness of the intermediate layer is 400-800 μm; And / or, the sheet size of the first graphene is 3-5 μm, and the sheet size of the second graphene is 1-5 nm.

4. The compression-resistant nano-carbon-based film material according to claim 3, characterized in that: The compression rate of the compression-resistant nano-carbon-based film material is 0.4-0.8 times.

5. A method for preparing a compression-resistant nano-carbon-based film material, characterized in that: include: Providing a first dispersion and a second dispersion, wherein a first graphene precursor is dispersed in the first dispersion, a second graphene and carbon nanotubes are dispersed in the second dispersion, and a sheet size of the first graphene precursor is larger than a sheet size of the second graphene; Using centrifugal casting, sequentially forming a first nanocarbon layer precursor from a first dispersion, forming an intermediate layer precursor from the first dispersion and a second dispersion, and further forming a second nanocarbon layer precursor from the first dispersion to obtain an initial assembly, and when forming the intermediate layer precursor, adjusting at least the flow rate of the first dispersion in a time sequence so that the distribution density of the first graphene precursor in the intermediate layer precursor has a decreasing trend away from the interlayer interface; performing a carbonization expansion treatment on the initial assembly to obtain a carbonized assembly; The carbonized assembly is graphitized to obtain a compression-resistant nano-carbon-based film material, wherein the first graphene precursor is converted into the first graphene.

6. The preparation method according to claim 5, characterized in that The complete process of centrifugal casting the intermediate layer precursor is divided into a continuous first stage and a second stage. In the first stage, the flow rate of the first dispersion decreases and the flow rate of the second dispersion increases. In the second stage, the flow rate of the first dispersion increases and the flow rate of the second dispersion decreases.

7. The preparation method according to claim 6, characterized in that In unit time, the mass change gradient of the first graphene precursor carried by the first dispersion is equal to the total mass change gradient of the second graphene and carbon nanotubes carried by the second dispersion.

8. The preparation method according to claim 5, characterized in that The mass concentration of graphene oxide in the first dispersion is 2.5-3 mg / mL; and / or, the mass ratio of the second graphene to the carbon nanotubes in the second dispersion is 1:0.6-1.2, and the concentration of the second graphene is 2.5-3 mg / mL; and / or, during the centrifugal casting, the flow rate of the first dispersion and / or the second dispersion is in the range of 0-1.67 mL / min; And / or, the rotation speed of the centrifugal casting is 0-20000 rpm.

9. The preparation method according to claim 5, characterized in that The carbonization expansion treatment is carried out in a protective atmosphere, with a maximum temperature of 1000-1800°C, a heating rate of 2-10°C / min, and a holding time of 60-120 min; And / or, the graphitization treatment is carried out in a protective atmosphere, with a maximum temperature of 2800° C., a heating rate of 2-10° C. / min, and a holding time of 60-120 min.

10. Use of the compression-resistant nano-carbon-based film material according to any one of claims 1 to 5 in chip packaging.

11. A chip packaging structure, characterized in that: It comprises a chip, the compression-resistant nano-carbon-based film material according to any one of claims 1 to 5, and a heat sink, wherein the compression-resistant nano-carbon-based film material is tightly filled between the chip and the heat sink, and the compression-resistant nano-carbon-based film material is in a mechanically compressed state.